The Development of Scaffolding Aided Learning Tools Using 5E Learning Cycle Model - Rody Putra Sartika; E. Enawaty; I. Lestari (Jurnal Pendidikan Indonesia, 2020)
Learning tools have important role to promote effective learning process. Available learning tools was still unable to construct good understanding for students especially in acid base topic. The aims of this study were to examine validity and application of tools and to describe improvement of students conceptual understanding before and after tools applied during learning process. Dick and Carey model was applied as research method. Data were collected by means of interview, observation, and test. Data were analyzed through descriptive qualitative analysis. According to data analysis, validity of lesson plan, worksheet, hand book and evaluation tools were 90,95%, 90,59%, 92,16%, and 97,14% respectively which categorized as very valid. The application of learning tools was 92,16% which categorized as very good. The improvement of students conceptual understanding was 0,57 which categorized as average. This research provides learning tools that enhance students conceptual understanding of the concept of acid-base topic.